Dietary Intervention Efficiency in Primary Care and Control of Metabolic Syndrome: A Systematic Review (Revista de Medicina Clinica, 2025)
Background: Metabolic syndrome is a major public health problem due to its association with type 2 diabetes and cardiovascular disease. This systematic review evaluates the effectiveness of dietary interventions in primary care to prevent or reverse MetS in adults. Methods: Studies published between 2000 and 2025, identified in PubMed, Scopus, and Web of Science, were included, following the PRISMA 2020 declaration. Clinical trials, prospective, and quasi-experimental studies with dietary interventions in primary care were analyzed. Methodological quality was assessed using RoB 2.0 and ROBINS-I. Results: Twelve studies with more than 22,000 participants were selected. Interventions based on the Mediterranean diet, with or without exercise, showed improvements in abdominal obesity, lipids, and blood pressure. Conclusions: Dietary interventions in primary care, especially those based on the Mediterranean diet, are effective in improving components of metabolic syndrome.
Keywords: Metabolic syndrome; Mediterranean diet; Primary care; Dietary interventions; Systematic review